2012
DOI: 10.1089/lap.2011.0412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Stress Response in Patients Undergoing Gynecological Laparoscopic Surgery Using Carbon Dioxide Pneumoperitoneum or Abdominal Wall-Lifting Methods

Abstract: Gynecological laparoscopic surgery using abdominal wall-lifting methods could avoid the deleterious effects of CO(2) pneumoperitoneum, and reduce the stress response. The lowest stress response was found when abdominal wall-lifting methods were used with the patient under epidural anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Van Hemelrijck et al, 1995;Han et al, 2012;Offinger et al, 2012) found decreased cortisol levels 45 minutes after the introduction of anaesthesia, which corresponds with our results. Stress steroid levels were lower in comparison to non-stress ones (e.g.…”
Section: Anaesthesia Influence On Adrenal Hormones Secretionsupporting
confidence: 92%
See 1 more Smart Citation
“…Van Hemelrijck et al, 1995;Han et al, 2012;Offinger et al, 2012) found decreased cortisol levels 45 minutes after the introduction of anaesthesia, which corresponds with our results. Stress steroid levels were lower in comparison to non-stress ones (e.g.…”
Section: Anaesthesia Influence On Adrenal Hormones Secretionsupporting
confidence: 92%
“…type of anaesthesia (mentioned above), handling, etc. Contrastingly, experimental measurements in human patients have found some differences in stress response for the same type of the laparoscopic intervention using a slightly different surgical approach (Han et al, 2012).…”
Section: Surgical Proceduresmentioning
confidence: 95%
“…16 In surgical planning for our case, we considered using gasless abdominal wall lifting instead of pneumoperitoneum, to avoid decreasing intra-abdominal blood flow. [17][18][19] However, the gasless abdominal wall-lifting method is suboptimal for diagnostic laparoscopy because it is more likely to result in a narrower laparoscopic field of view than pneumoperitoneum allows.…”
Section: Discussionmentioning
confidence: 99%
“…According to some articles, LUS is regarded as an important technique for laparoscopic surgeries such as liver tumor resection, biopsy of suspected nodules (metastases), and detection of bile ducts as expressed in [7][8][9]. Despite its early introduction, it has been rarely implemented in the past two decades [10].…”
Section: Introductionmentioning
confidence: 99%